Socio-Economic, Health and Ecological Sustainability of Vegetable Supplies in West African Cities: Assessment of Stakeholders’ Knowledge, Attitudes and Practices in Accra and Greater Lomé - Assinou, Kokou Elom; Kpotchou, Koffi (Journal of Ecohumanism, 2024)
In West Africa, vegetable supply chain development projects in Accra and Greater Lomé focus scarcely on the knowledge, attitudes and practices (KAP) of vegetable producers, traders and processors. Thus, the research aims to assess the level of sanitary, socio-economic and environmental sustainability of vegetable production, trade and processing in these cities, based on the knowledge, attitudes and practices of stakeholders. A quantitative multi-criteria evaluation approach was adopted, with reference to Global Reporting Initiative (GRI) standard 13 and Codex Alimentarius (CXC 1-1969 then CXC 53-2003). A sample of 303 people (156 in Accra and 147 in Greater Lomé) was formed using purposive sampling based on the assertion of E.R. Babbie (2016) and L. Kish (1965) combined with the comparison of S. Sudman (1976). Kobocollect and MS Excel respectively served to collect data and calculate KAP scores and percentages. Arcgis and Google Earth facilitated geographic representation of the data. The results reveal low rates of ecological (27.2%), health (26.9%), socio-economic (39.9%), technological and innovative (18.6%) KAP, evaluated at 28.6%. These results are unfavorable to the achievement of the SDGs. Hence the importance of an integrated, ongoing eco-nutritional education program for all stakeholders.